Data and analysis outputs for: Comparative co-expression reveals a regulatory core shared by angiosperm and conifer roots under cold - Aro, Tuuli; van Zalen, Elena M.; Vergara, Alexander; Canovi, Camilla; Kumar, Vikash; Chapple, Ellen Dimmen; Hvidsten, Torgeir R.; Hurry, Vaughan; Street, Nathaniel (Umeå University, 2026)
Underlying data, co-expression analysis outputs and results for the study "Comparative genomics of cold-temperature responses in boreal tree roots". Includes per-species root cold-stress expression matrices (Arabidopsis Col-0 and Ost-0, aspen, birch, Norway spruce, Scots pine), differential expression results, the comparative co-expression (ComPlEx) outputs and 15 pairwise comparisons, the conserved orthogroup core and cliques, supercluster/GO results, transcription-factor lists, annotation and sample metadata.
Keywords: Plant cell and molecular biology; Gene expression (incl. microarray and other genome-wide approaches); Genomics; Molecular evolution; Global change biology; Biological network analysis; Genomics and transcriptomics; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi; Genetics and Genomics; Genetik och genomik; Molecular Biology; Molekylärbiologi